CSR unconscious consumption by generation z in the COVID-19 era: Responsible heretics not paying CSR bonus? - Radka MacGregor Pelikánová; Martin Hála (Journal of Risk and Financial Management, 2021)
The COVID-19 pandemic brought a myriad of challenges and opportunities and has influenced the modern concept of sustainability as projected into the Corporate Social Responsibility (CSR) and the underlying multi-stakeholder model. The new generation of consumers, Generation Z, has progressively increased its participation in the market and its shopping trends have been impacting the entire CSR scenery. However, little is known about their attitudes, consumption preferences and expectations. In Spring 2021, this induced a pioneering case study survey involving members of Generation Z, students from a private university in Prague, focusing on their (lack of) readiness to pay any "CSR bonus". The principal research aim was to study and understand the rather surprising unwillingness of a solvent part of the new generation of consumers to support CSR during the COVID-19 era by paying at least a symbolic CSR bonus. A formal survey involving a questionnaire, replied to by 228 students, out of which 18 totally rejected the CSR bonus, was assessed via contingency tables. It was accompanied by a complementary questioning via an informal interview and glossing. This plethora of data was processed by meta-analysis and lead to an unexpected proposition: prima facie sustainability heretics denying to pay any CSR bonus can be conscious consumers and responsible and progressive supporters of the sustainability and CSR. Their rejection is a deontological cry in a desert for more transparency, trust and the rule of law.
Keywords: 330; COVID-19; sustainability; Corporate Social Responsibility (CSR); CSR bonus; Generation Z